PENINGKATAN CARA MENGATASI TERJADINYA KARIES GIGI SEHUBUNGAN DENGAN POLA MAKAN ANAK TK DI KECAMATAN KENJERAN KOTAMADYA SURABAYA - Tuti Kusumaningsih; M. Budi Rahardjo (Faculty of Dentistry, Universitas Indonesia, 2015)
The main objective of this activity was to provide counseling for the parents of kindergarten children to improve their understanding on the importance of knowledge to control dental caries related to children's diet behavior. In addition, this activity also provided training for children on Dental Health Education (DHE). Target group was the mother of kindergarten children in Kenjeran Sub district, Surabaya, who were expected to be able to apply knowledge they obtained, not only for their children, but also to others, for example, mothers who were involved in Posyandu and PKK activities. Participants of counseling were 160 individuals from 5 kindergartens, represented 5 villages in Kenjeran Subdistrict, Surabaya. Counseling was done via tutorial and visualization methods, followed by question-and-answer session, discussion, questionnaire filling, and evaluation. Training on how to brush tooth properly was given to the children. Pre-counseling questionnaire was falsely answered by 57.6% of the participants, and this number decreased drastically to 4.38% after counseling was given. DHE counseling and training for kindergarten children could be easily accepted. Motivation given could produce positive effects on cognitive knowledge of the mothers and on tooth brushing skill of the children. It is expected that teeth examination and counseling on dental health can be regulary dong in view of the absence of UKGS at kindergarten level.